The Association Between the Chronic Use of Non-Steroidal Anti- Inflammatory Drugs and Oxidative and Inflammatory Markers in the Elderly - Scheer Ely, Luisa; Gabriela Valle Gottlieb, Maria; Engroff, Paula; Gomes, Irenio; Noal Moresco, Rafael; Tatsch, Etiane; Vargas Bochi, Guilherme; Bueno Morrone, Fernanda; Attilio De Carli, Geraldo (Inflammation & Allergy-Drug Targets (Discontinued), 2014)
Objectives: Investigate the association between the chronic or occasional use of nonsteroidal anti-inflammatory drugs (NSAIDs) and plasma levels of oxidative and inflammatory markers in elderly at the Family Health Strategy in Brazil. Methods: It was a cross-sectional study of data collected from random elderly volunteers. A questionnaire including sociodemographic, health and medicine use data was administered. The blood levels of FRAP (ferric reducing ability of plasma), AOPP (plasma advanced oxidation protein products), MDA (malondialdehyde) and insulin were measured. Results: The study sample comprised 758 elderly patients, of which 121 (15.96%) used NSAIDs. The mean age was 68.53 years and 68.41 for individuals who used NSAIDs occasionally and chronically, respectively. Gastric problems may be associated with the chronic or occasional use of NSAIDs (P = 0.042). Which indicates mean plasma levels of Insulin and HOMA-IR (Homeostasis Model Assessment Insulin Resistance) are increased in chronic use of NSAIDs and describes a statistical trend (P = 0.065) for the association of chronic NSAIDs use with the BMI (body mass index) of the subjects studied. Conclusion: This study suggests that there is no association between the chronic or occasional use of NSAIDs and oxidative and inflammatory markers. It is known that NSAIDs have innumerable adverse effects, but they can have some benefits. So, additional studies are needed to clarify whether NSAIDs are associated with these markers and whether they are related with their real consequences.
Keywords: nonsteroidal anti-inflammatory drugs